Precise measurement of the line width of the photoassociation spectra of ultracold molecules by using a frequency shifter - 武寄洲 马杰 姬中华 张一驰 李玉清 汪丽蓉 赵延霆 肖连团 贾锁堂 (Chinese physics B, 2012)
We propose a technique to precisely measure the line width of the photoassociation spectra of the excited cesium molecule by using a frequency shifter to generate two laser beams with a precise frequency difference. A series of photoassociation （PA） spectra are recorded with two laser beam induced molecular lines, whose peak separation serves as an accurate frequency ruler to measure the line width of the PA spectra. The full width half maximum line width was studied as a function of PA laser intensity. The extrapolated value at zero laser intensity is （34.8± 0.22） MHz. By analyzing other broadening mechanisms, a value of （32.02 ± 0.70） MHz was deduced. It is shown that this scheme is inexpensive, simple, robust, and is promising for applications in a variety of other atomic species.